FEATURES OF POSTOPERATIVE PERIOD IN PATIENTS AFTER BRAIN REVASCULARIZATION - R. A. Vinogradov (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The aim of the research was to compare incidence of small complications after carotid endarterectomy (CEA) versus carotid artery stenting, as well as to evaluate its application in specific clinical situations. The outcomes of1826 patients who underwent surgery for stenosis of the internal carotid artery (ICA) were analyzed. There were two groups: 1018 patients who underwent CEA and 808 patients who carried the stenting. Age of patients was greater and coronary heart disease, diabetes, chronic obstructive pulmonary disease occurs more often in group with endovascular treatment, and they had rife stroke anamnesis. The mortality rate, uncontrolled hypertension and transient ischemic attacks were similar in early postoperative period. Stroke frequency was higher in patients with carotid artery stenting (35 (4,3 %) versus 27 patients (2,6 %) with CEA (p = 0,02)), and myocardial infarction took place more often after CEA (38 (3,7 %) versus 13 (1,6 %) patients with endovascular treatment (p = 0,008)). There was no statistically significant difference in security between CEA and stenting. However, treatment of carotid stenosis should be chosen according to individual characteristics, including individual anatomy.